Cytotoxic triterpenoid saponins from Clematis tangutica. (October 2016) - Zhao, Min; Da-Wa, Zhuo-Ma; Guo, Da-Le; Fang, Dong-Mei; Chen, Xiao-Zhen; Xu, Hong-Xi; Gu, Yu-Cheng; Xia, Bing; Chen, Lei; Ding, Li-Sheng; Zhou, Yan
Abstract: Eight previously undescribed oleanane-type triterpenoid saponins, clematangoticosides A-H, together with eight known saponins, were isolated from the whole plants of Clematis tangutica (Maxim.) Korsh. Their structures were elucidated by extensive spectroscopic analysis, in combination with chemical methods (acid hydrolysis and mild alkaline hydrolysis). Clematangoticosides D-G were found to be unusual 23, 28-bidesmosidic glycosides. The cytotoxic activities of all of the isolated saponins were evaluated against the four human cancer cell lines SGC-7901, HepG2, HL-60 and U251MG. Clematoside S, sapindoside B, kalopanax saponin A, and koelreuteria saponin A exhibited cytotoxicity against all of the test cancer cell lines with IC50 values in the range of 1.88–27.20 μM, while clematangoticoside D and F showed selective cytotoxicity against SGC-7901 with IC50 values of 24.22 and 21.35 μM, respectively. Graphical abstract: The phytochemical investigation of the Clematis tangutica extract yielded 8 previously undescribed triterpenoid saponins. Clematangoticosides D-G were the first examples of 23, 28-bidesmosidic glycosides found in the genus Clematis, and clematangoticoside D and F showed cytotoxicity against human cancer cell line SGC-7901. Highlights: Eight previously undescribed triterpenoid saponins were isolated from the whole plants of Clematis tangutica. Their structures were elucidated by extensive spectroscopic analysis and chemical method. The cytotoxic activities of all of the isolated saponins were evaluated. Clematangoticoside D and F showed selective cytotoxicities against SGC-7901.